Efektivitas PjBL-STEM Berbasis Proyek Filtrasi Air Terhadap Keterampilan Berpikir Kritis Siswa SMP - Melvin Aldila; Nasayabil Kamula; Jasmawati Jasmawati; Yulia Sukmawardhani; Sumiyati Saadah (STKIP HARAPAN BIMA, 2026)
This study aimed to determine the effectiveness of STEM-integrated Project-Based Learning (PJBL-STEM) in improving junior high school students’ critical thinking skills through a water filtration project. The study employed a quantitative approach with a one-group pretest-posttest design. The research subjects consisted of 47 ninth-grade students selected using a saturated sampling technique. Data were collected through a critical thinking skills test administered before and after the implementation of PJBL-STEM learning. The test was designed to measure students’ abilities in analyzing problems, evaluating information, and drawing conclusions based on scientific evidence. Data analysis was conducted using the N-Gain test to determine the level of improvement in students’ critical thinking skills after the implementation of PJBL-STEM learning. The results showed that the average pretest score of 63 increased to 92 in the posttest, with an N-Gain score of 79%, which falls into the high category. A total of 76.6% of students were categorized in the high N-Gain category, 21.3% in the medium category, and 2.1% in the low category. Students demonstrated improvements in identifying water quality problems, designing filtration tools, analyzing experimental results, and evaluating the effectiveness of their designs. These findings indicate that PJBL-STEM learning through a water filtration project is effective in enhancing students’ critical thinking skills and providing a more contextual science learning experience.